1994
DOI: 10.1002/poc.610070308
|View full text |Cite
|
Sign up to set email alerts
|

Competition between inter‐ and intramolecular hydrogen bonding in molecules with donor and acceptor groups. Solvatochromic and thermochromic evidence in n‐(nitrophenyl)alkylenediamines

Abstract: Solvent effects on the absorption spectra of N-@-nitrophenyl)dimethylenediamine (la), N-(p-nitropheny1)trimethylenediamine (Ib), N-@-nitrophenyl)tetramethylenediamine(Ic), N-methyl-N-@-nitropheny1)tetramethylenediamine (111, N-butyl-p-nitroaniline (111) and N-(o-nitropheny1)trimethylenediamine (IV) were studied at different temperatures. Whereas 11, Ill and 1V do not show any variation in their spectra characteristics with changes in temperature, I shows a hypsochromic shift with a hypochromic effect when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Second, the geometry of the bonded conformer affects the strength of the intramolecular hydrogen bond. For compounds with little conformational flexibility, such as ortho-substituted phenols, intramolecular hydrogen bonding is generally favorable when planar, five- or six-membered rings are formed, with six-membered ring structures being the more stable. , Likewise, for a series of flexible N- ( p- nitrophenyl)alkylenediamines, it has been reported that intramolecular hydrogen bonds do form, and that the strongest bond occurs for the molecule that is able to form a six-membered ring . The molecules in the present study all form either a five- or six-membered ring when in an intramolecularly hydrogen-bonded conformer.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Second, the geometry of the bonded conformer affects the strength of the intramolecular hydrogen bond. For compounds with little conformational flexibility, such as ortho-substituted phenols, intramolecular hydrogen bonding is generally favorable when planar, five- or six-membered rings are formed, with six-membered ring structures being the more stable. , Likewise, for a series of flexible N- ( p- nitrophenyl)alkylenediamines, it has been reported that intramolecular hydrogen bonds do form, and that the strongest bond occurs for the molecule that is able to form a six-membered ring . The molecules in the present study all form either a five- or six-membered ring when in an intramolecularly hydrogen-bonded conformer.…”
Section: Introductionmentioning
confidence: 50%
“…15,16 Likewise, for a series of flexible N-(p-nitrophenyl)alkylenediamines, it has been reported that intramolecular hydrogen bonds do form, and that the strongest bond occurs for the molecule that is able to form a six-membered ring. 17 The molecules in the present study all form either a five-or six-membered ring when in an intramolecularly hydrogen-bonded conformer.…”
Section: Introductionmentioning
confidence: 88%
“…1 the spectra of compound 14 corresponding to the tautomer A (Goya et al, 1988; see Scheme 2) at three different temperatures are shown as an example. This result suggests no chemical equilibrium (Giacomelli et al, 1994) at least in this short temperature range.…”
Section: Temperature and Concentration Effect Studiesmentioning
confidence: 78%
“…1 H‐NMR chemical shifts and signal strengths are very sensitive to hydrogen‐bond formation. In almost all cases, formation of a hydrogen bonds shifts the 1 H‐NMR signal downfield 36. Hydrogen bonds and the concurrent fast proton exchange contribute to widening of the resonance signal 37 .…”
Section: Resultsmentioning
confidence: 98%